the Study of some pro- inflammatory and Anti –inflammatory interleukins in diabetic patients - saad, enaas; Adnan, Dhuha; Alwan, Mohammed (ASJ - Academic Science Journal, 2024)
Objective; The objective of present research is evaluation roles of IL-38 and IL-39 indicators in pathophysiology of diabetic mellitus type II. Methods; The conducted investigation was occurred inside Bagdad capital during time period 1/8 to 30/11 month of 2023 year. Forty five (45) blood samples had from patients suffering from type II diabetes that attending outpatients clinics after screening them by specialist physician . Additionally, 45 blood samples were collected from individuals without disease and considered them as control group. All markers were quantified in all participants by utilize enzyme linked immunesorbent assay (ELISA) with kits provided from Bio-Sources International (Camarillo, CA, USA). Results of current investigation were calculated by SPSS v. 21.0 and Prism v.6 statistical software programs. Results; Findings of current investigation showed no significant differences (p>0.05) between study groups according to gender and age groups. Significant raise (p<0.05) levels of IL-38 and IL-39 in type II diabetic patients than healthy. ROC curve outcomes present the IL-38 showed highest sensitivity and specificity (96% and 95%) compared to IL-39 (sensitivity (80%) and specificity (75%)) at cut off (>251.21 and > 182.29) respectively in predicting individuals with diabetes mellitus type II with significant variation (p<0.05). Our outcomes showed no significant differences (p>0.05) between levels of IL-38 and IL-39 and gender as well as to age groups in patients with diabetes. Finally, pearson correlation coefficient results reveals no significant correlation (P>0.05) between IL-38 and IL-39 in diabetes patients . Conclusions; We concluded there is no effect of gender and age on diabetes mellitus. Increased levels of pro and anti-inflammatory interleukins (IL-39 and IL-38) in patients due to inflammation. Anti-inflammatory interleukin (IL-38) increased due to effect of pro- inflammatory interleukin (IL-39) to reducing the intensity of inflammatory reactions and preserving physiological equilibrium in essential organs. IL-38 is highly preferred in predicting diabetic patients than IL-39 due to it has highest sensitivity and specificity. There is no effect of gender and age on levels of these interleukins in DM patients. Finally, it is founded there is no significant correlation between IL-38 and IL-39 in those patients.